Johannesburg Central Park. Continuing the Urban Form through Landscape - Ziyambi, Christabel V. (University of the Witwatersrand, Johannesburg, 2025)
The urbanization process, up to early 2000s is the main cause of empty spaces – Andrea di Giovanni The research contributes to literature related to ‘urban voids’ in that it investigates the ‘anti-space,’ manufactured by the rail infrastructure site dividing Newtown and Braamfontein. The research investigates urban voids in the urban environment, discusses the mechanisms that are responsible for its production and the impact that the rail infrastructure site has had historically and still has for the city, its policy makers and users of the city. The terms ‘leftover,’ ‘urban void,’ and ‘anti-space,’ are used to describe sites that are, underused and neglected by the dominant patterns of use in the city. This is synthesized with literature on the urban regeneration of South African public space and landscape urbanism to create a framework that results in ‘landscape’ as a ‘positive urban void,’ facilitating urban cohesion.
A research report submitted in fulfillment of the requirements for the Masters in Urban Design, in the Faculty of Engineering and the Built Environment, School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Johannesburg Central Park; Urban Form; SDG-11: Sustainable cities and communities; SDG-13: Climate action